Synchronous Ileal Neuroendocrine Tumor and Ovarian Steroid Cell Tumor Present in a Female With Hyperandrogenism. (November 2016) - Gray, Stephanie; Chen, Yongxin; Litton, Tyler; Jallad, Bassel; Poddar, Nishant; Hoff, John T.; Schroeder, Katie; Taylor, Jason; Veerapong, Jula; Lai, Jin-Ping
Abstract : Well-differentiated neuroendocrine tumors (NET) of the ileum are generally slow-growing tumors with metastatic potential that may cause systemic symptoms from the secretion of serotonin, cortisol, and other biologically active substances. Likewise, steroid cell tumors of the ovary are slow-growing tumors that cause systemic symptoms from the functional production of androgens, estrogens, and other hormones. To the best of our knowledge, synchronous ileal NET and ovarian steroid cell tumors have not been previously reported in the English literature. We present a case of a 59-yr-old woman with 2 primary tumors that were found incidentally: a Stage III (T2N1M0) 1.6 cm well-differentiated NET (NET G2 ) of the terminal ileum with metastasis to a mesenteric lymph node and a 2.4 cm steroid cell tumor of the left ovary. The patient had suffered from hyperandrogenism for several years before diagnosis of an ovarian steroid cell tumor, but had no symptoms attributable to the NET. From review of the literature, this is the first case description of these 2 primaries arising in the same individual.